PENGARUH PERENCANAAN PAJAK DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2022 - Cahyani, Keken Suci Adi; Oktafiyani, Melati; Septriana, Ira; Herawati, Ratna (Faculty of Economic and Business Universitas STIKUBANK, 2023)
This analysis aims to examine the influence of tax planning and GCG on firm value in sector energy companies listed on the IDX for the period 2020-2022. The independent variable uses tax planning and GCG, while the dependent variable is firm value. Data obtained from consolidated financial reports of energy sector companies listed on the IDX for three research periods, namely 2020 - 2022, so that 51 samples were obtained for processing. Multiple liniear regression analysis was carried out to show the influence of the independent variable on the dependent variable. The results of the analysis show that tax planning has an effect on firm value, while institutional ownership, managerial ownership, independent commissioners and audit committees have no effect on firm value.